The Influence of CASA, FBI, LDR and BOPO on Digital Banking Profitability in Indonesia - Arvien Veda Aryanta Putera; Devia SS, Vietha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research uses qualitative methods by collecting data through interviews and documentation. This research aims to determine the impact of the Current Account Saving Account ratio, Fee Based Income, and Loan to Deposit ratio on the profitability of digital banking. This research uses quantitative method by collecting data using documentation techniques in the form of annual reports. The results of this study state that Current Account Saving Account (CASA) and Fee Based Income (FBI) partially have no significant effect on the profitability of digital bank, Loan to Deposit Ratio (LDR) has a significant positive effect on the profitability of digital bank, and Operational Cost to Operating Income (BOPO) has a significant negative effect on the profitability of digital bank. Simultaneously, the variable of Current Account Saving Account (CASA), Fee Based Income (FBI), Loan to Deposit Ratio (LDR), Operational Cost to Operating Income (BOPO) have a significant effect on the profitability of digital bank.